Ligand-Enabled Arylation of γ-C−H Bonds - Li, Suhua; Zhu, Ru-Yi; Xiao, Kai-Jiong; Yu, Jin-Quan (Angewandte Chemie International Edition, 2016)
PdII‐catalyzed arylation of γ‐C(sp3)−H bonds of aliphatic acid‐derived amides was developed by using quinoline‐based ligands. Various γ‐aryl‐α‐amino acids were prepared from natural amino acids using this method. The influence of ligand structure on reactivity was also systematically investigated. PdII‐catalyzed arylation of γ‐C(sp3)−H bonds of aliphatic acid‐derived amides was developed by using quinoline‐based ligands. Various γ‐aryl‐α‐amino acids were prepared from natural amino acids using this method. The influence of ligand structure on reactivity was also systematically investigated.